Associations of dwelling characteristics, home dampness, and lifestyle behaviors with indoor airborne culturable fungi: On-site inspection in 454 Shanghai residences. (June 2016) - Wang, Xueying; Liu, Wei; Huang, Chen; Cai, Jiao; Shen, Li; Zou, Zhijun; Lu, Rongchun; Chang, Jing; Wei, Xiaoyang; Sun, Chanjuan; Zhao, Zhuohui; Sun, Yuexia; et al.
Abstract: From March 2013 to December 2014, we collected air samples of airborne culturable fungi from 454 residences with young children (mean age: 6.9 years-old) in Shanghai, China. We also measured indoor air temperature and relative humidity, and compiled information regarding dwelling characteristics, lifestyle habits, and dampness-related indicators. Mean concentrations (mean ± SD) of culturable fungi in the child's bedrooms ( n  = 445) and in the living rooms ( n  = 436) were 310 ± 313 (range: 6–3184) cfu/m 3 and 300 ± 288 (range: 19–3044) cfu/m 3, respectively. The concentrations of airborne fungi were higher in spring and winter than in other seasons, but were only slightly correlated with indoor air temperature and relative humidity in any season. Higher levels of airborne culturable fungi in the child's bedroom were significantly associated with location in a rural area, constructed before 2000, ground/top floor of the residential building, and building area <10 m 2 . Among those residences inspected in winter, rooms with poor ventilation and residences with spiders and cockroaches, damp spots and moldy spots on the wall surface were associated with higher concentrations of indoor airborne culturable fungi. We found that the household level of airborne fungi was acceptable in most of Shanghai's current residences. The possibility of indoor airborne culturable fungi during cold spring and winter requires more attention than in other seasons. Preventing dampness-related damage, improving indoor ventilation, and maintaining a dwelling free of spiders and cockroaches may decrease indoor level of airborne culturable fungi. Highlights: On-site inspection on indoor airborne fungi was conducted in 454 Shanghai residences. Household level of airborne fungi was acceptable in most of residences in Shanghai. Concentration of airborne fungi in spring and winter was higher than in other seasons. Indoor temperature and relative humidity had little effect on household airborne fungi. Damp damages, low ventilation, and pets had notable effect on indoor airborne fungi.